La Lettera di Macario di Gerusalemme e la questione di battisteri nell’Armenia paleocristiana - Garibian, Nazénie (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
In studies dedicated to the history of Armenian architecture, it is traditionally accepted that in Armenia there where no baptisteries as independent structures or arranged as a separate rooms attached to the main church. Yet, in the countries adjacent to Armenia, such as Northern Syria, Mesopotamia, and Georgia, the use of such baptisteries was a widespread phenomenon during the early Christian period. The paper aims to open the debate on this topic with the analysis of literary documents and, first of all, the Letter to the bishops of Armenia by Macarius of Jerusalem (314-335/36), addressed in 335. The obtained results invite scholars to reexamine the archaeological data collected so far on Armenian early Christian monuments with a view to re-evaluating the possible presence of such baptisteries.